Pengaruh Operating Leverage Dan Financial Leverage Terhadap Laba Per Lembar Saham: Studi Pada Perusahaan Manufaktur Yang Tercatat Di Jakarta Islamic Index Periode 2018-2022 - Ahmad Joki Rustandi; Efni Anita; Firman Syah Noor (STIKes Ibnu Sina Ajibarang, 2024)
This research is motivated by the complex relationship between operating leverage, financial leverage, and earnings per share (EPS) in the context of corporate finance. This research aims to analyze the impact of operating leverage and financial leverage on earnings per share in manufacturing companies listed on the Jakarta Islamic Index during the period 2018-2022. Utilizing financial data from the sample companies, the study adopts a quantitative approach with regression analysis using Eviews to evaluate the relationship between operational and financial leverage with the performance of earnings per share. The research results indicate that operating leverage does not have a significant effect on earnings per share, with a partial test probability value of 0.9744 > 0.05. Financial leverage also does not have a significant effect on earnings per share, with a partial test probability value of 0.7368 > 0.05. Simultaneously, operating leverage and financial leverage do not have a significant effect on earnings per share, with a simultaneous test probability value of 0.94578 > 0.05. The calculation of the coefficient of determination shows that the independent variables in the model fail to explain the variation in the dependent variable well. Subsequent research is recommended to increase the sample size of manufacturing companies listed on the JII and replace insignificant independent variables with others that can significantly influence earnings per share.